Effects of Financial Incentives, Performance Appraisal, and Employee Recognition on Work Motivation of Start-Up Employee - Puspitasari, Mariana Diah (IJBLE Scientific Publications Community Inc., 2024)
This study examines the effects of financial incentives, performance appraisal systems, and employee recognition on work motivation among employees in start-up environments. Utilizing a sample of 300 start-up employees, data were analyzed using descriptive statistics, reliability analysis, correlation analysis, and multiple regression analysis with SPSS software. The results indicate that all three factors—financial incentives, performance appraisal systems, and employee recognition—positively and significantly influence work motivation, with financial incentives having the strongest impact. Interaction effects analysis further reveals that the combined impact of these factors is greater than their individual effects, suggesting a synergistic relationship. The study's findings underscore the importance of a holistic approach to employee motivation, integrating financial rewards, effective performance evaluations, and meaningful recognition to enhance motivation and organizational performance in start-ups.